Peningkatan Transparansi Tata Kelola Keuangan Desa melalui Pengembangan Sistem Berbasis Web dengan Menerapkan Model Agile - Septiano Cepeda Da Costa; Galet Guntoro Setiaji; Ahmad Rifa'i (Bulletin of Computer Science Research, 2025)
This research discusses village financial management as a primary aspect in supporting village progress and community welfare. Transparent and effective budget management is crucial for ensuring that village funds are utilized optimally for development programs. However, several obstacles persist, including delays in financial reporting and limited access to information for residents. The purpose of this research is to design and develop a web-based village financial information system using the Laravel framework and an Agile methodology to improve transparency, data accessibility, and the effectiveness of real-time financial reporting. The Agile method was selected for its iterative and collaborative development process, which is responsive to user needs. This approach allows both residents and village officials to participate actively in the development process, ensuring the resulting system serves as a viable solution to existing problems. Functional testing results using the Black Box method indicate that the system facilitates easier financial reporting, provides accurate data presentation, and supports accountability in village fund management. This system is expected to increase community participation in budget oversight and serve as a technological solution for the digitalization of village financial management. Ultimately, this system aims to make village budget management transparent, fast, and accessible to all residents at any time, thereby fostering community trust and engagement in village development.